2012
DOI: 10.1118/1.4729709
|View full text |Cite
|
Sign up to set email alerts
|

VMAT QA: Measurement-guided 4D dose reconstruction on a patient

Abstract: Even for a well-commissioned TPS, comparison metrics show better agreement on average to MGDR than to TPS on the arbitrary-shaped measurable "patient." The method requires no more accelerator time than standard QA, while producing more clinically relevant information. Validation in a heterogeneous thoracic phantom is under way, as is the ultimate application of 4D MGDR to virtual motion studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
144
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 99 publications
(146 citation statements)
references
References 30 publications
2
144
0
Order By: Relevance
“…Volumetric comparisons were based on the measurement‐guided dose reconstruction with an independent dosimeter (ACPDP). This 3D dose reconstruction method is by now thoroughly validated, including direct, full 3D, gel dosimetry 17 , 25 , 27 . It provided a satisfactory level of agreement at the 2%/2mm level with both direct Delta 4 measurements at the diodes' locations and D4 Interpolation (Table 1).…”
Section: Discussionmentioning
confidence: 84%
See 3 more Smart Citations
“…Volumetric comparisons were based on the measurement‐guided dose reconstruction with an independent dosimeter (ACPDP). This 3D dose reconstruction method is by now thoroughly validated, including direct, full 3D, gel dosimetry 17 , 25 , 27 . It provided a satisfactory level of agreement at the 2%/2mm level with both direct Delta 4 measurements at the diodes' locations and D4 Interpolation (Table 1).…”
Section: Discussionmentioning
confidence: 84%
“…This method, called ArcCHECK planned dose perturbation (ACPDP), was described in detail and evaluated previously on geometrical and anthropomorphic phantoms using dose sampling with ion chambers, film, and optically stimulated luminescence dosimeters 17 , 25 , 26 . Recently, a full 3D dose ACPDP validation with BANG3 polymer gel (MGS Research, Guilford, CT) was also reported (27) …”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Electronic portal imaging devices (EPIDs) have also been tested for in vivo dosimetry purposes (12) . In phantom, verification of the treatment plan in three dimensions (3D) can be carried out successfully using Delta 4 (Scandidos AB, Uppsala, Sweden), (23) ArcCHECK (Sun Nuclear Corp.), 5 , 24 , 25 , 26 and Octavius (PTW, Freiburg, Germany) (27) …”
Section: Introductionmentioning
confidence: 99%